Stationary Universe in General Relativity and Lyra's Geometry - Singh T.; Agrawal A.K. (My University, 2025)
The stationary universe solutions have been studied using the metrics of VAN Stockum (1937) and Gödel (1949) in a New ST theory (Saez and Ballester, 1985), general relativity with variable cosmological term (Narlikar et al., 1991), Lyra's geometry (Sen, 1957) and Cosmic strings. It has been shown that the stationary universe has rigid rotation in ST theory. In the presence of variable cosmological term, there is non‐rigid rotation in the presence of Zeldovich fluid for van Stockum metric. In Lyra's geometry the only solution is possible when the gauge function β is variable and there is Zeldovich fluid. However, in the presence of cosmic strings, there is no solution with van Stockum or Gödel metrics. Copyright © 1994 WILEY‐VCH Verlag GmbH & Co. KGaA